Low Vision Aids: Visual Outcomes and Barriers in Children with Low Vision - V. R. Venkataramanan; Sairani Karanam; Vinaya Kumar Konana; Sudhakar Potti; Netra Harsha; S. Shruthi (Delhi Journal of Ophthalmology)
Aims: To study the demographic profile, cause of low vision, visual outcome and the barriers in using low vision aids (LVA). Design: Prospective observational clinical study. Methods: This study was performed on 50 children aged 10-17 years who attended LVA clinic. Unaided, best corrected acuity was assessed using ETDRS chart for distance and Bailey – Lovie chart for near. For distance tasks, telescopes were tried and for near tasks, magnifiers and high plus glasses were tried, improvement in vision was noted. Reasons for not purchasing low vision aids were noted. Results: Reading black board was the most common first priority in 31 (62%) children. Reading small and medium prints was the most common second priority in 30 (60%) children. Outdoor games (n=14, 28%) was the most common third priority of low vision children. Macular dystrophy (42%) was the major cause of low vision. With LVA, 64% of children could improve to log MAR 0.5 or better for distance and 44 (88%) children could read N6 to N12. Out of 24 children who did not purchase LVA, cost (n=7) and cosmetic blemish (n=7) were main barriers. Conclusion: There was significant improvement in both near and distance visual acuity with LVA. There is a need for LVA to be made available free of cost for the under privileged and for the devices to be made more cosmetically acceptable. Preventable cause for low vision can be eliminated by creating awareness in public.